Awareness on HIV/AIDS among the Blood Donors of a City Hospital - Sultana, Niru (Ibrahim Medical College Journal, 2010)
This descriptive cross-sectional study was carried out on ‘HIV/AIDS awareness' among the blood donors of Dhaka Medical College Hospital. The aim of the study was to assess the level of awareness among blood donors on HIV/AIDS and to assess their knowledge regarding its prevention and control. A total of 110 (87.3% male, 12.7% female) donors participated in this study. Their mean age was 24.9 ± 5.2 years. More than 60% of the respondents had primary or secondary level of education. Two-thirds (66.11%) of them donated blood for their relatives, while the rest did it for donation's sake. Although 93.6% of the respondents heard about AIDS (TV being the most common source), none had a good or excellent level of awareness about the disease. About mode of transmission, 20.9% had average and very few had a good level of knowledge regarding its prevention. When asked for an opinion about the country's risk for HIV/AIDS, more than half (54.2%) had the view that the country was at a risk from the disease and nearly three quarters (72.5%) were of the opinion that mass awareness campaigns on HIV/AIDS could improve the situation. Ibrahim Med. Coll. J. 2009; 3(2): 63-66 Key Words: HIV/AIDS, blood donors, awareness, Bangladesh DOI: 10.3329/imcj.v3i2.4219